EXCOMP : Sistem Pakar untuk Mendiagnosa Kerusakan Komputer dan Memberikan Saran Perbaikan - Hindayati Mustafidah; Hendrik Prawijaya; Dwi Ayanto (JUITA : Jurnal Informatika, 2011)
Expert system is one of the sciences of artificial intelligence that resembles the behavior of an expert in solving a problem. Expert systems have been developed in various fields of science. In the research developed an expert system (EXCOMP) to perform diagnostics on the computer damage and suggest improvements that are interactive. Knowledge of computer damage was collected from various sources: books, internet, and computer technicians. Someone who experienced his computer suddenly does not operate normally, can utilize EXCOMP to help diagnose early damage and provide suggestions for improvement